Trail Making Test Can Evaluate the Impairment of Papez Circuit System by the Infarction of Anterior Nuclei of the Thalamus- A Case Report - Tempaku, Akira (Eastern Green Neurosurgery, 2026)
Papez circuit contributes memory formation. Papez circuit disorder is difficult to evaluate the severity, since the appropriate estimation tool is not established. Executive function is also supported by the memory dependent behaviors. The author found that trail making test (TMT), which is known to check the executive function, can contribute the evaluation of the severity of Papez circuit dysfunction. Case presentation: A 78-year-old man had ischemic infarction at the anterior nuclei of thalamus. He showed the decreased cognitive function without motor nor sensory disorders. Executive function including activity of daily living (ADL) was also impaired. TMT score was markedly increased than that score, that had been obtained at two years ago. Conclusion: Anterior nuclei of thalamus is a component of Papez circuit. Ischemic disorder of that region brings memory disturbance. Further, ADL has been influenced by declining memory. Because of executive function depends on retrieve the memory for the sequential activities, TMT score changes clearly showed the impairment of Papez circuit function.